Barabaro '89. - Progetto Giovani, Firenze; Flux, Liège (Firenze : Progetto Giovani, 1989)
Alves Pereira, Manuel ; Charlier, Jean-Claude ; Cloet, Mark ; De Greef, Rudolf ; Desmet, Emile ; Devreux, Pierre ; Fink, Christoph ; Gasparotto, Paolo ; Geurts, Frédéric ; Hanssen, Roland ; D'Hondt, Lieve ; Medart, François ; Melis, Anne-Mie ; Michielsen, Bart ; Morrens, Peter ; Parisi, Joseph ; Pillonetto, Franck ; Ponlot, Marianne ; Stricanne, Virginie ; Van Buggenhout, Chris ; Van Deplassche, Guy ; Wittek, Anne-Marie
Barabaro '89, Progetto Giovani, Firenze / Flux, Liège, 29.10.1989 - 28.11.1989
boek